2020
DOI: 10.5296/jas.v8i2.17075
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil of Ocimum basilicum and Eugenol as Sedatives for Nile Tilapia

Abstract: This study evaluated the modulation of the ventilatory frequency of Nile tilapia sedated with essential oil of Ocimum basilicum and eugenol. The fish were exposed to the following treatments: control (water only); ethanol 200 µl L-1 (concentration used to dilute the anesthetic); eugenol 10 µl L-1 and 20 µl L-1; essential oil of O. basilicum at the concentration of 10 µl L-1 and 20 µl L-1. After 90 minutes of exposure to the treatments, water quality, mortality and respiratory rate were determined. The concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…basilicum , essential oil contain high levels of estragole (72.57%) and linalool (21.60%). Similarly, Ventura et al (2020) noted that major constituents of the O . basilicum essential oil were methyl chavicol (estragole) (66.51%) and linalool (20.90%).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…basilicum , essential oil contain high levels of estragole (72.57%) and linalool (21.60%). Similarly, Ventura et al (2020) noted that major constituents of the O . basilicum essential oil were methyl chavicol (estragole) (66.51%) and linalool (20.90%).…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, it was determined that basil, O. basilicum, essential oil contain high levels of estragole (72.57%) and linalool (21.60%). Similarly, Ventura et al (2020) noted that major constituents of the O.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Studies reported that the best concentration of O. gratissimum essential oil can induce anesthesia in O. niloctilus juveniles ranging from 90 to 150 mg/L [25], while other authors reported a concentration between 60 and 100 mg/L [26]. The experimental study showed that the essential oil of O. basilicum at 20 µL/L can induce mild sedation without loss of balance and ventilation in Nile tilapia juveniles [27]. Other studies showed an anesthetic effect of eugenol at low dosages of 20 µL/L [28] and at a higher dosage of 60 mg/L [29].…”
Section: Discussionmentioning
confidence: 94%